MODELING OF ACTIONS TO TAKE AFTER A SCORPION STING AND DEVELOPING A WEB BASED INFORMATION SYSTEM TO TRACK THE DIFFERENT INDICATORS SYSTEMATICALLY - El Malhi, Abdelghani; Nekkal, Nesma; Eloufir, Rhizlane; Echchelh, Adil; Soulaymani, Abdelmajid; Mokhtari, Abdelrhani; Rassam, Ahmed; Soulaymani Bencheikh, Rachida (European Scientific Journal, ESJ, 2014)
To take the quickest and the correct decision when a scorpion stingsis decisive in terms of patient rescue. Based on a long experience andcollected information about envenomation, Anti Poison andPharmacovigilance Center of Morocco (CAPM) developed a guideline withclear actions to help the patients.European Scientific Journal April 2014 edition vol.10, No.12 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431118The application of information technology in health sector has grownexponentially over the last years. This research aimed to model a health caresystem and make it easier to use by the health professionals. It will allow theclinician to monitor the evolution of the different vital signs and eventuallysuggest the best hospitalization (type of drug, reanimation, release...). Themain objective is to improve effectiveness and efficiency.The developed application contains sensible data, therefore the generalconcept is constructed to be secure. Furthermore, it is web oriented, in orderto facilitate the communication between the various sanitaire structures. Theprogram helps enormously to gather important statistics and analysis.